When do European election campaigns become about Europe?. Issue 7 (19th July 2021) - Eugster, Beatrice; Jalali, Carlos; Maier, Michaela; Bathelt, Severin; Leidecker-Sandmann, Melanie; Adam, Silke; Negrine, Ralph; Demertzis, Nicolas
Abstract: This article examines which parties included European issues in their 2014 European Parliament campaigns, and what influenced whether they did so, based on innovative data from the content analysis of 9, 100 press releases in seven countries. Overall, established and especially governing parties no longer shied away from EU issues, referring to them as often as challenger parties did. The likelihood of EU issues in campaigns derives from a combination of predictors from the selective emphasis and co-orientation approaches. In general, parties with high internal dissent on EU integration avoid European issues, and weak leaders will only dare talk about the EU if internal dissent is low. However, between-party-type comparisons indicate that successful leaderships of governing parties facing strong internal divisions are even less likely to put EU issues on the agenda. With respect to the co-orientation model, parties' EU focus seems to be mainly determined by the communication of (other) opposition parties.